Integrating School Makerspaces into the English Language Arts Curriculum - Lou Lahana (Middle Grades Review, 2021)
School Makerspaces have shown great potential to foster powerful learning outcomes for students, including the enhancement of creative problem-solving abilities, the nurturing of “soft skills” such as grit and leadership, as well as deep STEAM knowledge development. Within the school context, however, little attention has been given to how Makerspaces can promote social activism. Students hold passionate views on issues, such as homelessness, e-cigarette smoking, domestic violence, plastic pollution, and street harassment. How can Makerspaces provide an environment that promotes personal learning and self-expression so that these passions take form as social activism? This practitioner perspective details the implementation of a Social Action-Themed Makerspace within a New York City middle school. The author, the school’s Makerspace coordinator, outlines the pedagogical practices used to promote personalized learning, namely the presentation and framing of social issues to students, the centrality of personal choice, the curation of resources to facilitate research, and the freedom of access to tools and materials for product creation. Student learning outcomes are presented, including student-produced documentaries, songs, craftwork, and art pieces. The article concludes with practical challenges for School Makerspace coordinators, as well as future directions that may increase the impact of such spaces.
Keywords: personalized learning; social justice; social activism; middle school; makerspace; young adolescents